Electrolyte Derangements and Its Association with Mortality in Stroke Patients in the University College Hospital, Ibadan, Nigeria (African Journal of Biomedical Research, 2020)
Stroke is a leading cause of morbidity and mortality worldwide, and it is likely to worsen in developing countries over the next two decades based on the projections by the World Health Organization (WHO 2005). A high level of mortality and morbidity in stroke patients has been recorded with coexisting comorbidities like Infections, cerebral oedema, hyperglycemia and electrolyte derangements. Data on electrolyte derangements in stroke patients still remain somewhat scanty till date. The study was aimed at determining whether complications of stroke include electrolyte derangements, and what relationship it has with mortality of stroke patients. A total of 98 stroke patients were enrolled in this observational study after considering all relevant inclusion and exclusion criteria, A detailed history and examination was performed on patients, samples for Electrolyte, Urea and Creatinine were taken from patients, Patients were followed for a period of one month and those discharged before a month were followed up on phone to determine their current status at home. There was a greater incidence of stroke in males as compared to females with a male: female ratio of 4.39:1, A higher mortality was also seen in males of which the older age group accounted for more than half of the cases. Azotaemia and Hypercreatinemia accounted for the most frequent electrolyte derangements. There was no statistically significant difference between proportion of those who died with abnormal electrolyte and proportion of those with abnormal electrolyte that survived. The high level of electrolyte derangements in stroke patients is a call for more studies to determine the role of electrolytes in the mortality of stroke patients